The Influence of Internal and External Factors on Nigerian Foreign Policy Formulation and Implementation - Dickson, Blessing Sunday (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
State behaviour internationally has long been understood to be the result of various factors that emanate both from the state itself and its constituting external environment. The influence of these factors tends to vary between states. Using the case of Nigeria, this thesis set out to determine whether internal or external factors are deterministic for Nigerian foreign policy. Following a review of the literature on sources of foreign policy and an overview of Nigerian foreign policy through history, evidence of relevant sources in relation to Nigerian foreign policy was presented and subsequently used as a basis for formulating interview questions. The resulting evidence was then taken in conjunction with the answers to the interview questions in the hope of finding evidence in support of the thesis hypotheses, which collectively predicted that internal influence takes dominance over external influence where Nigerian foreign policy is concerned. As expected, findings indicate that internal influence on Nigerian foreign policy has been more pervasive than external influence. This, however, does not mean that external influence has been non-existent or entirely secondary but that the majority of Nigerian foreign policy behaviours can be explained primarily by internal considerations.

ÖZ: Devletlerin uluslararası sistemdeki davranışları hem uluslararası etkenlerden hem de devletlerin kamuoyu gibi içsel etkenlere dayandığı uzun zamandır kabul görmektedir. İç ve dış etkenlerin etkinlik boyutu devletler arasında farklılık göstermektedir. Bu tez, Nijerya‟yı bir vaka çalışması çerçevesinde inceleyip, iç ve dış etkenlerin Nijerya dış politikasındaki belirleyiciliğini tespit etmeyi hedeflemiştir. Tezde öncelikle, kapsamlı bir literatür taraması ile farklı düşünce okullarına göre dış politika kaynaklarının tipolojisi çıkartılmış. Akabinde Nijerya‟nın dış politikasının tarihsel süreçler içerisinde nasıl değiştiği tespit edilmiştir. Bu bulgular uzmanlarla yapılan mülakatların temelini oluşturmuş ve tezde birincil kaynakların kullanımını tezin tümdengelim tasarımına uygun olarak yapılmasını sağlamıştır. Böylelikle hem ikincil hem de birincil kaynaklar kullanılarak kuramlara dayalı hipotezler test edilmiştir. Araştırma sonuçları, Nijerya dış politikasının kamuoyu odaklı iç etkenlere dayalı olduğunu, iç etkenlerin dış etkenlerden daha belirleyici olduğunu göstermiştir.
Master of Arts in International Relations. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of International Relations, 2017. Supervisor: Assist. Prof. Dr. Berna Numan.
Keywords: International Relations; Nigeria--Foreign relations; Foreign policy; Nigeria; Unit-Level; Foreign Policy Analysis; Case Study